Ocena bieżącej płynności finansowej przedsiębiorstwa na przykładzie sektora budowlanego - Mioduchowska-Jaroszewicz, Edyta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Liquidity ratios measure the firm's ability to meet short term debts and indicate the long time cash flow. A study carried out among construction companies, between 1997 and 2005, indicated that there are companies having normative as well as negative or positive liquidity. The liquidity of the companies was measured using ratio: current liabilities. Whether this is the best method of ratio measurement or not is arguable. The author proposes a new method which relies on annual financial reports. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 300-307